Development and evaluation of Food friends get movin' with mighty moves™: a physical activity program to prevent obesity in low-income preschoolers - Bellows, Laura Leigh, author; Anderson, Jennifer, advisor; Auld, Garry, committee member; Kennedy, Catherine, committee member; Davies, Patricia, committee member (Colorado State University. Libraries, 2007)
The prevalence of overweight among preschool-aged children in the United States is increasing at an alarming rate. The preschool years provide an opportunity to establish healthful eating and physical activity behaviors which can lessen the growth of obesity. Unfortunately, preschoolers have been largely ignored when it comes to obesity prevention efforts. The overall objective of this project was to design, develop, and evaluate a physical activity program to compliment the Food Friends ® nutrition program in an effort to prevent overweight in young children. Food Friends Get Movin' with Mighty Moves™ is an 18 week program focusing on gross motor development, physical fitness, and physical activity in the classroom environment. This project utilized the steps of social marketing to develop the Mighty Moves™ program. Further, to enhance the likelihood that behavior change would occur, the Social Learning Theory was embedded within the social marketing framework. The Food Friends Get Movin' with Mighty Moves™ study was a randomized controlled trial of 3- to 5-year old children (n=201) enrolled in 8 Head Start centers in Colorado. On-site measures included height, weight, physical fitness (sit-ups, sit-n-reach, shuttle run, 3-minute run), and gross motor skill (Peabody Developmental Motor Scales) assessments. BMI, BMI z-score and BMI percentiles were calculated. Additionally, physical activity was assessed by pedometers over a 6-day timeframe (4 weekdays and 2 weekend days), and daily step counts were recorded by parents. Characteristics of the study population indicated a high prevalence of overweight, low physical activity levels, and average to below-average motor skills. The intervention did not have an effect on weight status but did improve gross motor skills and fitness levels. Lastly, no difference was found for physical activity by treatment. The success of Mighty Moves™ at increasing gross motor skills and physical fitness in preschoolers, in concert with the Food Friends® program's demonstrated ability to increase children's willingness to try new foods, has contributed to the establishment of healthful behaviors for proper growth and development in the early years. These behaviors serve as foundations to building healthy lifestyles, which may decrease the risk of overweight later in life.
Keywords: Obesity in children -- Prevention; Exercise for children; Preschool children